2017
DOI: 10.1108/jmd-06-2016-0117
|View full text |Cite
|
Sign up to set email alerts
|

Researchers as enablers of commercialization at an entrepreneurial university

Abstract: Purpose The purpose of this paper is to explore and visualize alternative ways – how and by whom – that academic research can come into commercial use. Design/methodology/approach This study in the Swedish context investigates one entrepreneurial university, Chalmers University of Technology. In total, 18 interviews were conducted about researchers’ views on commercialization and on how research comes into commercial use. Findings Five propositions are advocated in relation to researchers’ role as enablers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
1
22
0
1
Order By: Relevance
“…Researchers deeply expect that collaborative research can increase the practitioners´ adoption of their research results (Decter et al 2007;Berggren 2017;Rajaeian et al 2018). If age and seniority do not influence the researchers' collaboration with industry, universities could take advantage by facilitating the processes and encouraging researchers to collaborate with firms.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers deeply expect that collaborative research can increase the practitioners´ adoption of their research results (Decter et al 2007;Berggren 2017;Rajaeian et al 2018). If age and seniority do not influence the researchers' collaboration with industry, universities could take advantage by facilitating the processes and encouraging researchers to collaborate with firms.…”
Section: Discussionmentioning
confidence: 99%
“…Davidsson (1989) found that there is a positive relation between achievement and growth willingness for growth-oriented entrepreneurs. During this exploitation phase, these entrepreneurs need to draw on networks to support their new ventures, such as alumni networks (Berggren, 2017). However, university-based entrepreneurs face barriers in exploiting their opportunities (Davey et al, 2016;O'Kane et al, 2017) and also often have skill, expertise, and competence gaps.…”
Section: A Conceptual Organizing Frameworkmentioning
confidence: 99%
“…To find a single definition of the Entrepreneurial University which works across the European Higher Education Area is difficult and controversial" [9]. The characteristics of entrepreneurial universities are described interestingly by several authors [10][11][12][13][14][15][16][17][18][19][20][21][22]. In the article we shall try to analyze the scientific literature referring to the experience of different countries on entrepreneurial universities in several directions, namely: 1.…”
Section: Entrepreneurial University: a Brief Literature Reviewmentioning
confidence: 99%